2006
DOI: 10.1080/03124070600986002
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Clients From Harm: The Role of Continuing Professional Education

Abstract: In the absence of professional regulation and in the context of a changing and competitive environment, the Australian Association of Social Workers (AASW) encourages member commitment to self-regulation and continuing professional education (CPE). Continuing professional education is promoted as the platform upon which the credibility of the entire profession of social work and the maintenance of high-quality standards of practice rest. High practice standards are integral to the protection of vulnerable peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Smith et al (2006) suggested that informal learning methods are often favored over formal ones, with an understanding that CE also requires mechanisms to recognize and regulate these activities. In line with social work literature that supports CE as a means to maintain the credibility of the profession and foster market competiveness (Kent, 2006), this report shows that it is important for a CE model to focus on service quality control and professional development. It implies that CE is indeed a CPD process that engages social work practitioners, researchers, educators, and policy analysts in planning in order to provide leadership in this collaborative effort.…”
supporting
confidence: 62%
“…Smith et al (2006) suggested that informal learning methods are often favored over formal ones, with an understanding that CE also requires mechanisms to recognize and regulate these activities. In line with social work literature that supports CE as a means to maintain the credibility of the profession and foster market competiveness (Kent, 2006), this report shows that it is important for a CE model to focus on service quality control and professional development. It implies that CE is indeed a CPD process that engages social work practitioners, researchers, educators, and policy analysts in planning in order to provide leadership in this collaborative effort.…”
supporting
confidence: 62%
“…Learning does not end with graduation from formal education, particularly in a field like social work where lifelong learning is both a key value and a necessity for informed practice. Professional development around values and ethics is critical to the promotion of social justice, protection of clients, and as a response to ideological threats to the social work perspective evident in the contextualizing environment in which the profession operates (Kent, 2006). An experience like the "two grocery stores" assignment could be replicated in various community settings, guided by structured facilitation, and followed up with an inperson debriefing to ensure that participants have the opportunity to make meaningful connections between their experiences and underlying social structures.…”
Section: Discussionmentioning
confidence: 99%
“…Italy has a compulsory register (Fargion 2008), while in New Zealand registration is on a voluntary basis (Orme & Rennie 2006). Social workers in Australia are not registered, although the Australian Association of Social Workers encourages self-regulation (Kent 2006). In Iceland, only holders of the centrally recognised master's qualification are allowed to use the legally protected title of social worker (Strauss 2008).…”
Section: Policy Contextmentioning
confidence: 99%